2017
DOI: 10.1177/2050312117694938
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on treatment satisfaction and health perception in children and adolescents with type 1 diabetes mellitus on multiple daily injection of insulin, insulin pump and sensor-augmented pump therapy

Abstract: Objectives:Diabetes management imposes considerable demands on patients. Treatment method used has an impact on treatment satisfaction. We aim to examine the relationship between treatment satisfaction and health perception with the method used for treatment of type 1 diabetes mellitus in children and adolescents.Subjects and method:We have interviewed patients with type 1 diabetes mellitus using questionnaires to assess treatment satisfaction and health perception. Patients were divided into three groups base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 21 publications
3
10
0
1
Order By: Relevance
“…The main caregivers in the CSII group were highly satisfied with their child's diabetes regimen, significantly more so than those whose child stayed on MDI. High satisfaction with CSII is also reported by other studies, 40 among these RCTs. 21,33 The initial HbA1c values of the study sample as a whole were satisfactory.…”
Section: Discussionsupporting
confidence: 83%
“…The main caregivers in the CSII group were highly satisfied with their child's diabetes regimen, significantly more so than those whose child stayed on MDI. High satisfaction with CSII is also reported by other studies, 40 among these RCTs. 21,33 The initial HbA1c values of the study sample as a whole were satisfactory.…”
Section: Discussionsupporting
confidence: 83%
“…A study was conducted in UAE to see if there can be better health perception and patient satisfaction after treatment, if insulin pumps were used by children and adolescents (91). The authors found that it provides more value in terms of treatment and satisfaction, irrespective of the duration of use of the insulin pumps.…”
Section: Resultsmentioning
confidence: 99%
“…Authors concluded that augmenting pump therapy with sensor use added value to treatment satisfaction without correlation with the duration of the sensors use. [14] fMDI was not compared in the study. In addition to the types of insulin regimen and delivery systems, other factors which potentially impact parental satisfaction include the method of administration of MDI, presence of CGM, sensor augmented pump systems and artificial pancreatic system (closed loop system).…”
Section: Discussionmentioning
confidence: 99%